Economic evaluation of extended electrocardiogram monitoring for atrial fibrillation in patients with cryptogenic stroke. Issue 7 (October 2021) - Chew, Derek S; Rennert-May, Elissa; Quinn, F Russell; Buck, Brian; Hill, Michael D; Spackman, Eldon; Manns, Braden J; Exner, Derek V
Background: Timely identification of occult atrial fibrillation following cryptogenic stroke facilitates consideration of oral anticoagulation therapy. Extended electrocardiography monitoring beyond 24 to 48 h Holter monitoring improves atrial fibrillation detection rates, yet uncertainty remains due to upfront costs and the projected long-term benefit. We sought to determine the cost-effectiveness of three electrocardiography monitoring strategies in detecting atrial fibrillation after cryptogenic stroke. Methods: A decision-analytic Markov model was used to project the costs and outcomes of three different electrocardiography monitoring strategies (i.e. 30-day electrocardiography monitoring, three-year implantable loop recorder monitoring, and conventional Holter monitoring) in acute stroke survivors without previously documented atrial fibrillation. Results: The lifetime discounted costs and quality-adjusted life years were 206, 385 and 7.77 quality-adjusted life years for conventional monitoring, 207, 080 and 7.79 quality-adjusted life years for 30-day extended electrocardiography monitoring, and 210, 728 and 7.88 quality-adjusted life years for the implantable loop recorder strategy. Additional quality-adjusted life years could be attained at a more favorable incremental cost per quality-adjusted life year with the implantable loop recorder strategy, compared with the 30-day electrocardiography monitoring strategy, thereby eliminating the 30-day strategy by extended dominance. The implantable loop recorder strategy was associated with an incremental cost per quality-adjusted life year gained of 40, 796 compared with conventional monitoring. One-way sensitivity analyses indicated that the model was most sensitive to the rate of recurrent ischemic stroke. Conclusions: An implantable loop recorder strategy for detection of occult atrial fibrillation in patients with cryptogenic stroke is more economically attractive than 30-day electrocardiography monitoring compared to conventional monitoring and is associated with a cost per quality-adjusted life year gained in the range of other publicly funded therapies. The value proposition is improved when considering patients at the highest risk of recurrent ischemic stroke. However, the implantable loop recorder strategy is associated with increased health care costs, and the opportunity cost of wide scale implementation must be considered.